An improved plate culture procedure for the rapid detection of beer‐spoilage lactic acid bacteria. Issue 2 (10th January 2014) - Deng, Yang; Liu, Junyan; Li, Huiping; Li, Lin; Tu, Jingxia; Fang, Huijing; Chen, Jiang; Qian, Fei
<x xml:space="preserve">Abstract</x> Lactic acid bacteria (LAB) are the most frequently encountered beer‐spoilage bacteria, and they can render beer undrinkable owing to the production of lactic acid, diacetyl and turbidity. Three beer‐spoilage strains, 2011–6, 2011–8 and 2011–11, were isolated from finished beers. Based on the 16S rRNA sequence analysis, these three isolates were identified as Lactobacillus acetotolerans. Only the horA homologue was detected in these strains, while the horC homologue was not detected. In addition, an improved plate culture method for the rapid detection of beer‐spoilage LAB by the addition of catalase was evaluated. Supplementation with catalase enhanced the growth and colony sizes of the spoilage LAB investigated. These beer‐spoilage bacteria, including some slowly growing strains, were detected within five days of incubation using the modified method. Taken together, the modified procedure could be a rapid countermeasure against beer‐spoilage LAB, and it compared favourably with the conventional plate culture method. Copyright © 2014 The Institute of Brewing & Distilling